Mechanical and biomechanical measurements of five currently available osteosynthesis systems of self-tapping screws - B. Saka (Blackwell Synergy, 2000)
Craniofacial fractures often have a certain pattern, indicating the weak points in the bones. The fractured bone may vary from less than 1 mm to more than 7 mm thick. These variations require the screws inserted to have specific physical and technical properties.